2019
DOI: 10.3897/compcytogen.v13i4.35572
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype characteristics, chromosomal polymorphism and gene COI sequences of Chironomus heteropilicornis Wülker, 1996 (Diptera, Chironomidae) from the South Caucasus

Abstract: The study presents data on the karyotype characteristics, features of chromosomal polymorphism and the gene COI sequences of Chironomus heteropilicornis Wülker, 1996 (Diptera, Chironomidae) from the South Caucasus. We found 8 banding sequences in the Caucasian population. Overall, The Caucasian population of the species can be characterized as having a low level of polymorphism. We found one new banding sequence hpiA2 in the banding sequence pool of Ch. heteropilicornis. We observed inversion polymorphism only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Phylogenetic analysis using COI sequences showed groups of related species (Fig. 2), which concur with how these species were combined into the groups earlier on the basis of karyological and morphological traits (Kiknadze et al 2016;Karmokov 2019). Obtained data are highly accurate (~100%) and show that Ch.…”
Section: Dna-barcoding and Phylogenetic Analysissupporting
confidence: 79%
“…Phylogenetic analysis using COI sequences showed groups of related species (Fig. 2), which concur with how these species were combined into the groups earlier on the basis of karyological and morphological traits (Kiknadze et al 2016;Karmokov 2019). Obtained data are highly accurate (~100%) and show that Ch.…”
Section: Dna-barcoding and Phylogenetic Analysissupporting
confidence: 79%
“…Nucleoli were found in arms B, D, E and G, Balbiani rings in arms B and G. The homologues in arm G usually laying closely to each other or are tightly paired (Kiknadze et al 2016). (Kiknadze et al 2016;Karmokov 2019) and one new hpiB2 sequence reported for the first time (Fig. 3).…”
Section: Karyotype Of Chironomus Heteropilicornis Wülker 1996 From the Gydan Peninsulamentioning
confidence: 74%
“… heteropilicornis , hpiB2, was found. The hpiA2 banding sequence was found in all individuals, and this is its second finding after the Georgian population ( Karmokov 2019 ). The hpiF3 banding sequence was found only in the homozygous state.…”
mentioning
confidence: 77%
See 2 more Smart Citations